PENGARUH DOPING CHROMIUM TERHADAP SIFAT KRISTALINITAS DARI NANOPARTIKEL α-Fe2O3 (HEMATITE) - Novia Magdalena Purba; Erwin Amiruddin; Salomo Sinuraya; Krisman Sabar (Komunikasi Fisika Indonesia, 2023)
This study aims to determine the crystal structure and particle composition as well as the effect of iron oxide nanoparticles (α-Fe2O3) doped chromium for methylene blue degradation. Iron oxide nanoparticles were obtained by 3 stages of ball milling with the total time milling of 120 hours. Each stage of ball milling, the product was process by strong NdFeB magnet uin order to separate between iron oxide and non iron oxide phases. The last product of ball milling process is called BM 3. The BM 3 product was divided into 4 parts with the same amount of weight namely BM 3A, BM 3B, BM 3C, and BM 3D with variations in the concentration of 0 wt.% chromium; 5 wt.%; 10 wt.%; and 20 wt.% These samples were characterized using X-ray diffraction (XRD) method and X-ray fluorescence (XRF). The XRD measurements show that the BM 3 product has a Hematite (α-Fe2O3) phase with a Rhombohedral structure. The crystal size of the samples decreases with increasing chromium concentration. The amount of Fe decreases from 57.316% to 54.204% as  chromium increases from 0 wt.% to 5 wt.% respectively. Meanwhile, the percentage of Cr increases before being doped with 0.08% chromium and then increases after being doped with 5 wt.% chromium to 7.758%.